Successful treatment with guanfacine in a long‐COVID case manifesting marked cognitive impairment - Tsuyoshi Kondo; Riki Higa; Mariko Kuniba; Hotaka Shinzato; Yoshikazu Takaesu (Wiley, 2024)
Abstract Background Persistent cognitive impairment is a serious consequence of the post‐COVID condition. However, there have been no established effective treatments for this pathophysiology supported by sufficient evidence. Case Presentation A 32‐year‐old woman became aware of difficulty in word recalling, reading, and writing as well as difficulty in completing various household multitasks 3 weeks after the COVID‐19 infection. Although blood tests, magnetic resonance imaging, electroencephalography, and Kohs block design test were all within normal limits, completion time by trail making test (TMT) A or B was markedly delayed. Finally, she was referred to our hospital 3 months after the infection. At baseline, the THINC integrated tool (THINC‐it), a digital battery consisting of the five‐item version of the perceived deficit questionnaire (PDQ‐5), choice reaction time (CRT), 1‐back test, digit symbol substitution test (DSST), and TMT‐B, revealed poor capability in attention, working memory, and executive function. Also, near‐infrared spectroscopy (NIRS) demonstrated no activation in frontal or temporal regions during verbal fluency task. Extended‐release guanfacine (GXR) 2 mg/day was initiated and a month later was elevated up to 4 mg/day as a maintenance dose. The PDQ‐5, CRT, 1‐back test, DSST, and TMT‐B were dramatically improved 1 month after GXR treatment. NIRS finding was also normalized after 2 months of treatment. These effects were successfully maintained throughout the 6‐month follow‐up period. Conclusion GXR may be helpful in improving subjective/objective cognitive functioning and frontotemporal brain activity in long‐COVID patients manifesting apparent cognitive impairment.